Biochemical characterization of thioredoxin reductase from Babesia bovis - Regner, Erika Lucía (2014)
This paper addresses the identification, cloning, expression, purification and functional characterization of thioredoxin reductase from Babesia bovis, the etiological agent of babesiosis. The work deals with in vitro steady state kinetic studies and other complementary analyses of the thioredoxin reductase found in the pathogenic protist. Thioredoxin reductase from B. bovis was characterized as a homodimeric flavoprotein that catalyzes the NADPH-dependent reduction of Trx with a high catalytic efficiency. Moreover, the enzyme exhibited a disulfide reductase activity using DTNB as substrate, being this activity highly sensitive to inhibition by Eosin B. The thioredoxin reductase/thioredoxin system can reduce oxidized glutathione and S-nitrosoglutathione. Our in vitro data suggest that antioxidant defense in B. bovis could be supported by this enzyme. We have performed an enzymatic characterization, searching for targets for rational design of inhibitors. This work contributes to the better understanding of the redox biochemistry occurring in the parasite.